Usuń nawiasy i wykonaj redukcję wyrazów podobnych.

a) 12(x+3)-5x(4-3x)

b) 3(a-3b)-4(2b-4x)

c) 2-10(2y-x)+2(-y+4x)

d) 3(-2+y)-(x-2y)-2(x+y)


Odpowiedź :

Odpowiedź:

a)    12 ( x+3) - 5x ( 4-3x)= 12x +36 -20x + 15x²=-8x +36+15x²

b)   3 ( a-3b) -4 ( 2b-4x)= 3a -9b-8b +16x=3a -17b +16x

c)   2-10( 2y-x) +2 ( -y +4x)= 2 -20y +10x -2y +8x= 2 -22y +18x

d)   3 ( -2 +y) - ( x-2y) -2 ( x+y)= -6+3y -x +2y -2x -2y= -6 +3y -3x

Szczegółowe wyjaśnienie:

a)12(x+3)-5x(4-3x)=12x+36-20x+15x^2=15x^2-8x+36

b)3(a-3b)-4(2b-4x)=3a-9b-8b+16x=3a-17b+16x

c)2-10(2y-x)+29-y+4x)=2-20y+10x-2y+8x=2-22y+18x

d)3(-2+y)-(x-2y)-2(x+y)=-6+3y-x+2y-2x-2y=-6+3y-3x